The Relationship Of Placenta Retension, Age And Distance Of Birth With Post Partum Blooding Events In Rsud Dr. Hm Rabain Muara Enim 2021 - Ervita Desi Marina; Siti Aisyah Hamid; Erma Puspita Sari (Science Midwifery, 2022)
Post partum hemorrhage is blood loss of more than 500 ml through the birth canal that occurs during or after the delivery of the placenta. Postpartum hemorrhage is one of the contributors to 80% of maternal deaths in addition to infection, high blood pressure during pregnancy, and unsafe abortion. The purpose of this study was to determine the relationship between retained placenta, age, and birth spacing with the incidence of postpartum hemorrhage at Dr.HMRabain M.Enim Hospital in 2021. The research method used was an analytical survey method with a cross sectional approach. Data analysis using chi-square test. The results showed retained placenta (p value = 0.000, OR 124.667), age (p value = 0.001, OR 5.278), and birth spacing (p value = 0.025, OR 9.808). Conclusion: There is a relationship between retained placenta, age and birth spacing simultaneously with the incidence of postpartum hemorrhage at Dr. HMRabain M. Enim in 2021. It is recommended for health workers to further improve public education about postpartum hemorrhage and related factors. with the incidence of postpartum hemorrhage so that the public understands so that it can reduce the incidence of postpartum hemorrhage. age and birth spacing simultaneously with the incidence of postpartum hemorrhage at Dr. HMRabain M. Enim in 2021. It is recommended for health workers to further improve public education about postpartum hemorrhage and related factors. with the incidence of postpartum hemorrhage so that the public understands so that it can reduce the incidence of postpartum hemorrhage.